Integration of Environmental Education in Islamic Religious Education Curriculum: A Sustainable Education Perspective - Muhammad Wahyu; Juliani; Khairul Hidayat; Abdi Fadillah; Dio Septiawan; Kliven Brem Ginting (Yayasan Zia Salsabila, 2024)
Environmental education plays an important role in creating awareness of sustainable life amidst global challenges related to ecosystem damage. One strategic effort to instill this awareness is through the integration of environmental education into the Islamic Religious Education (PAI) curriculum. This article aims to examine how the concept of environmental education can be integrated into PAI as part of sustainable education. This study highlights the potential of religious values, such as amanah, responsibility, and harmony with nature, in forming a generation that cares about the environment. Through a holistic approach, this integration not only teaches religious knowledge but also builds students' ecological awareness based on the principles of Islamic spirituality and morality. The results of the study show that this integration requires comprehensive curriculum planning, policy support, and training for educators to be able to implement relevant and applicable learning approaches. With proper implementation, environmental education in PAI can be an integral part in forming a generation that plays an active role in preserving nature for the sake of human survival.